A Comprehensive Analysis of the Medicinal Use of Bioactive Secondary Metabolites from the Genus Ehretia - Kaur, Amanpreet; Shukla, Abha; Arora, Sarika; Pandey, Trapti; Pokhriyal, Priyanka (Recent Developments in Chemistry and Biochemistry Research Vol. 2, 2024)
The roughly 150 species of plants that make up the genus Ehretia are primarily found in tropical regions of North America, Africa, Australia, and Asia. They have long been used as traditional and folk remedies in China, India, and Japan to cure a wide range of illnesses. Pharmacological investigations verified that the genus's crude extracts or specific components had anti-snake venom properties in addition to antioxidant, anti-inflammatory, antibacterial, anti-arthritic, anti- tubercular, and anti-allergic properties. Based on the available literature up to February 2024, summery of secondary metabolites that have been identified from several species of Ehretia in this literature. Chapter concentrated on the known biological activities of the Ehretia plants and covered them in detail here, in addition to their traditional therapeutic usage.